Equity Issues and Return Volatility - Larrain, Borja; Varas, Felipe (Review of Finance, 2013)
Abstract We show that the repurchaser–issuer return spread is stronger among stocks with high return volatility. Rational and behavioral theories predict that this finding is the product of risk volatility and sentiment volatility, respectively. However, our results are inconsistent with these theories as they currently stand. Loadings on standard risk factors do not follow the dynamics that would explain the return predictability related to issuance decisions. If we sort on a stock's beta with respect to the aggregate sentiment index of Baker and Wurgler (2006, J. Finance, 61, 1645–1680), which proxies for sentiment volatility, the results are weaker—economically and statistically—than when sorting on return volatility.